Litigio o arbitraje: ¿una competencia? Disputa comercial transfronteriza de adjudicación en un mundo (2017)
Cross-border civil and commercial conflicts can be adjudicated by courts of sovereign states or in a private setting, namely by arbitration panels. Against the background of a globalizing world and an increase in popularity of arbitration as a means of dispute resolution ‘Europe’ (the European Union) faces the challenge to demarcate borderlines as litigation in court and arbitration tend to get in conflict more often. Conflicts may relate to the jurisdiction of courts versus the competence of arbitration panels (inter alia resulting in anti-suit court orders or even arbitral awards), as well as to the recognition of foreign court orders being capable of frustrating arbitral awards or vice versa. This contribution attempts to analyze how these clashes ought to be resolved under the reign of ‘new’ cross-border civil and procedural law in Europe (EU Regulation 1215/2012, or ‘Recast’) on Jurisdiction and Recognition of Foreign Judgments in Civil and Commercial Matters’ (in force January 15, 2015). Two preliminary rulings of the Court of Justice of the European Union (CJEU) though still interpreting EU Regulation 44/2001 (i.e. the legislative predecessor of the Recast), remain important to the law regime of the Recast. The final conclusion is that, even though the Recast respects the international law framework of notably the 1958 New York Convention on the recognition and enforcement of arbitral awards, a considerable amount of legal uncertainty remains, as Recital 12 of the Recast Preamble contains ‘open-ended’ parameters leaving discretionary room for national law of each individual EU Member State and calling for further interpretative rulings of the CJEU.